RE LAYOUT TATA LETAK FASILITAS TERHADAP OPTIMALISASI JARAK DAN ONGKOS MATERIAL HANDLING DENGAN MENGGUNAKAN ALGORITMA ALDEP PADA PT. BUMI SARANA BETON - Taufiq, Ahmad Ramadhan; Pawennari, Andi; Padhil, Ahmad (Jurnal Ilmiah Teknik dan Manajemen Industri, 2023)
Facility layout is an integrated planning of the flow or flow of components of a product (goods and or services) in an operating system (manufacturing and or non-manufacturing) in order to obtain the most effective and efficient interrelation between workers, materials, machinery and equipment as well as the handling and transfer of materials, semi-finished goods, from one part to another (a good layout is a layout that has a small material handling cost, so that the optimal production facility layout will reduce the distance of movement and the cost of material handling. PT.Bumi Sarana Beton is one of the companies that needs to improve the layout of its production facilities. Improvements will be made by redesigning the facilitation layout using the ALDEP Algorithm method with the help of ALDEP software, to identify interrelated interests between the selected facilities as the method used in solving facility layout problems. Based on the results of analysis and discussion, it can be concluded that the calculation using ALDEP, the software produces 5 iterations of alternative proposals. From the resulting proposal alternative, one of the best proposals is chosen that has the largest TCR value, which is in the alternative 4 with a TCR value of 768, so the layout generated by the ALDEP algorithm has a minimum distance and displacement time of 1,674 m within 59.38 minutes. And produce the smallest OMH, which is Rp. 371,736,90, so that the proposed layout that is produced is optimal. In the end, the company needs to make improvements to the layout in the production process because there is a department that has a long distance, resulting in large material handling costs